Students' Perception toward the Use of Pair Work Strategy in Writing Descriptive Text at Senior High School Level - Ririn Divarianti; M. Fadhly Farhy Abbas (LPPM STBA Persada Bunda, 2024)
Learning difficulties become one of inhibiting factors in the learning process, to produce a good quality of writing, students have various options of writing strategies. This study aims to find out students' perception toward the use of pair work strategy in writing descriptive text at SMA smart Indonesia. The method of this research was descriptive quantitative research with survey design. This research was conducted from December 2021 to January 2022. The instruments used in this research were questionnaire which consisted of 16 items. Data were analyzed by using descriptive statistics in the form of summation of scores, mean, standard deviation and then interpreted descriptively. The result of the findings revealed that the students have high level perception. It was proved by the mean score, benefit gained 4.23. Learning Improvement gained 4.26, and motivation gained 4.37. Overall, students' perception toward the use of pair work strategy in writing descriptive text have a positive and categorized into very high average score was 4.27. In conclusion, pair work strategy in the writing learning process provided more opportunities for students to be more active in the learning process and pair work can develop students' writing skills because pair work provided significant benefits for students, especially in the learning process in SMA Smart Indonesia.